AVALIAÇÃO EM LÍNGUA PORTUGUESA NO ENSINO FUNDAMENTAL: CRENÇAS EXISTENTES E RESISTENTES - Martins, Simone de Fátima Colman (2016)
This work presents an investigation and analysis on the beliefs about how to evaluate of Portuguese teachers as first language, whom work in a private school system (Ponta Grossa/PR) which establishes that the evaluations should be held jointly by teachers. Through our research we want to demonstrate the influences of social context, historical, economic and mostly political in the educational field as well as of the laws governing education. The analyzes reinforce belief evaluate that is rooted in the subjects that make up society, beliefs perpetuated by various social environments and the school, perhaps the main one. Countless works and authors reflect and analyze the evaluation in the educational context, however, there are few works that reflect and ask about beliefs evaluate in the LP as first language, so we base in research that accost beliefs evaluate a LE ( BARCELOS, 1995, 2001, 2004, 2006; ROLIM, 1998; FLAIN - FERREIRA, 2005; BARATA, 2006; AVILA , 2013). We lead our research showing the historical context and policy on the evaluation (COSTA, 2004; DIAS SOBRINHO, 2002; VIANNA , 2002; GARCIA, 2013; LIMA FILHO, 2013) and the historical context of teaching in LP (SILVA; CYRANKA 2009; BUNZEN, 1999; RAZZINI, 2000; SOARES, 2004, 2011; ARAUJO, 2014). In this perspective, the project aims to specifically investigate and analyze the beliefs of these teachers about what is to work in groups and the beliefs evaluate of these teachers. We search also to analyze the beliefs evaluate the LP of those teachers and beliefs about single evaluation / standardization of evaluation of these teachers. Methodologically, the research is qualitative and data were obtained through two meetings with teachers and semistructured interviews. To participate in the meetings and interviews were invited Portuguese teachers who work from 6th to 9th year and participate in the process of preparation of evaluations together. We note that the process of preparation of evaluations together is extremely complex because it involves confrontation and divergence of ideas concerning personal relationship issues, but also of the academic education, of treatment contents, among other factors and require the permanent establishment in the form of work. As a result, we present the following positions: for the teachers to work in group is to deal with criticism, to work ‘equal’ and to interact; assess is to know whether the teacher taught and the students learned; assess LP is to assessing grammar and interpretation of texts; a only one evaluation unites the group, ensures the ‘same’ job and the same performance both the teacher and the student. Through reflections that consider language as a social practice and as a constituent of the subjects and of history, we hope to have contributed to the studies related to beliefs in teaching of the LP as first language.